2019
DOI: 10.1186/s12974-019-1430-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron accentuated reactive oxygen species release by NADPH oxidase in activated microglia contributes to oxidative stress in vitro

Abstract: Background Excessive iron contributes to oxidative stress after central nervous system injury. NADPH oxidase (NOX) enzymes are upregulated in microglia after pro-inflammatory activation and contribute to oxidative stress. The relationship between iron, microglia, NOX, and oxidative stress is currently unclear. Methods We evaluated the effects of iron on lipopolysaccharide (LPS)-activated microglia and its secondary effect within neuronal co-cultures. Further, NOX2 and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 46 publications
(44 reference statements)
5
59
1
Order By: Relevance
“…Previous studies have demonstrated that microglia produced intracellular ROS via NADPH oxidase under oxidative stress conditions [30]. To verify whether AOPPs, which are oxidative stress products, could cause excessive ROS production in BV2 cells, the intracellular ROS levels in AOPPs-treated BV2 cells were examined.…”
Section: Aopps Regulated Bv2 Cells To Generate Intracellular Ros Via mentioning
confidence: 99%
“…Previous studies have demonstrated that microglia produced intracellular ROS via NADPH oxidase under oxidative stress conditions [30]. To verify whether AOPPs, which are oxidative stress products, could cause excessive ROS production in BV2 cells, the intracellular ROS levels in AOPPs-treated BV2 cells were examined.…”
Section: Aopps Regulated Bv2 Cells To Generate Intracellular Ros Via mentioning
confidence: 99%
“…Central nervous system. Impaired iron homeostasis in the CNS is coupled with neuroinflammation, oxidative stress, neurodegenerative disease pathology, and cognitive decline (100)(101)(102)(103). Accordingly, iron must be tightly regulated on a cell-to-cell basis to ensure normal homeostatic function.…”
Section: Tissue Mɸs Regulate Iron Homeostasis and Tissue Functionmentioning
confidence: 99%
“…Of note, however, microglia are not impervious to iron overload-induced damage. Excessive iron can trigger microglial release of proinflammatory cytokines (such as TNF-α, IL-6, and IL-1β) and/or accentuate production of ROS that disturbs the function of adjacent cell types (101,104,114,116). Microglia are iron loaded in active lesions of multiple sclerosis (118), and activated microglia are associated with increased iron uptake and retention in models of neurodegenerative disorders, such as Alzheimer's and Parkinson's disease (107,109,114,(118)(119)(120).…”
Section: Tissue Mɸs Regulate Iron Homeostasis and Tissue Functionmentioning
confidence: 99%
“…Another hallmark of active lesions is disruption of the blood-brain barrier (BBB), combined with leukocyte infiltration into the CNS (Kuhlmann et al, 2017;Grajchen et al, 2018). As a consequence, reactive microglia start synthesizing ROS, resulting in local oxidative stress, DNA damage, and neurotoxicity (Hametner et al, 2013(Hametner et al, , 2018Yauger et al, 2019). These iron-laden microglia have the tendency to stay in this proinflammatory state, impairing clearance of myelin debris, making it harder for oligodendrocytes to migrate toward the lesion site and, as a result, complicating remyelination processes (Mairuae et al, 2011;Lee et al, 2019).…”
Section: Microglia In Ms Lesion Pathologymentioning
confidence: 99%